Metatranscriptomic Analyses Unravel Dynamic Changes in the Microbial and Metabolic Transcriptional Profiles in Artisanal Austrian Hard-Cheeses During Ripening - Quijada, Narciso Martín; Dzieciol, Monika; Schmitz-Esser, Stephan; Wagner, Martin; Selberherr, Evelyne (Frontiers in Microbiology, 2022)
Vorarlberger Bergkäse (VB) is an artisanal Austrian washed-rind hard cheese produced from alpine cows’ raw milk without the addition of ripening cultures. Ripening time is a key factor in VB, as it strongly influences the microbial communities present in the cheeses and the organoleptic properties of the product. In this study, the microbial and metabolic transcriptional profiles in VB rinds at different ripening times were investigated. VB products before (30 days of ripening) and after (90 days of ripening) selling were selected, RNA was extracted and subjected to shotgun metatranscriptomic sequencing. The analysis revealed some of the previously described abundant bacterial taxa of Brevibacterium, Corynebacterium, Halomonas, Psychrobacter and Staphylococcus to be highly active in VB rinds. Additionally, the investigation of most important metabolic pathways in cheese ripening clearly showed differences in the gene transcription profiles and the active microbiota between the two ripening points investigated. At 30 days of ripening, metabolic events related with the degradation of residual lactose, lactate, citrate, proteolysis and lipolysis were significantly more transcribed and mainly associated to Staphylococcus. On the other hand, genes involved in the degradation of smaller compounds proceeding from previous metabolism (i.e. metabolism of free amino acids and fatty acids) were significantly more expressed in VB rinds with 90 of ripening, and mainly associated to Brevibacterium and Corynebacterium. These latter metabolic activities are responsible of the generation of compounds, such as methanethiol and 2,3-butanediol, that are very important for the flavor and aroma characteristics of cheeses. This study shows the dynamic changes in the gene transcriptional profiles associated to energy substrates metabolism and the generation of organoleptic compounds during VB ripening and uncovers bacterial taxa as key drivers of the ripening process. These taxa might be the target for future studies towards an accelerated cheese ripening and the enhancement of its organoleptic properties.